Media, Culture and Society in Putin's Russia
XIII, 248 p.
Keywords: An international collection of papers focused on media, culture and society in postcommunist Russia. Contributors deploy a wealth of primary data in examining the kinds of issues that are central to our understanding of the kind of system that has been established in the world's largest country after a period of far-reaching change.